THE PASTORAL PROFILE OF FATHER IOAN SABĂU REFLECTED IN THE DOCUMENTS FROM THE ARCHIVES OF SECURITY - JORJA, Nifon (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2017)
Father Ioan Sabau (1941-2009) had been a worthy priest and confessor of his faith who has built a grandiose church, such as a cathedral, in Vinerea, Alba county, during a full communist era. The hallowing of this church had been the excuse of arresting Father Ioan, but the real reason for which he was taken into the Security attention was the guilt of completely achieving his priestly mission. The Father’s prosecution from the CNSAS archive contains almost 850 pages, from which it can be distinguished the pastoral face of father Ioan Sabau, his qualities and his diligences. If we bear in mind that all the hard work of the informers of the Securitate was to find reasons to compromise the father, we do understand that the value of these confessions is given by the fact that they were some of the Father’s enemies.